POLITIK SEBAGAI JALAN KEBAHAGIAAN: REFLEKSI FILSAFAT SOSIAL DAN POLITIK ISLAM AL-Fß¥╣Rß¥╣B─¬ - Putri, Endrika Widdia (Alfuad: Jurnal Sosial Keagamaan, 2020)
This article departs from the problem that the happiness of a country and its citizens lies in its politics. Whatever politics adopted by a country are all good. However, it is the human skills that govern politics that affect the course of politics. If those who manage are capable, then good politics will improve with the human skills that govern it - and vice versa. Departing from these problems, this article will look at how good politics in the eyes of philosophers. In particular, al-F─ür─üb─½ political thought - 9th century Muslim philosopher who lived during the Abbasid Dynasty. Al-F─ür─üb─½ with its main state (al-Mad─½nah al-F─üdhilah) argues that the ideal state is a sovereign state to create a prosperous society based on the principles of equal rights, freedoms, and human unity. Al-F─ür─üb─½ with political thought succeeded in expressing universal values of politics, and was able to map out the state classifications that existed in his day and did not rule out the possibility of existing today and formulated 12 (twelve) criteria for an ideal leader. In addition, al-F─ür─üb─½ is considered a Muslim philosopher who began to talk about democracy. Although, al-F─ür─üb─½ himself does not mention the term democracy except al-mad─½nah al-jama'iyyah which is defined as a democratic state. Although al-F─ür─üb─½ is not practical politics, his political thought is the result of his deep knowledge and experience. This is enough to prove that his political thinking is worth knowing and scrutinizing.